2010
DOI: 10.3109/03602530903491683
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic OATP and OCT uptake transporters: their role for drug-drug interactions and pharmacogenetic aspects

Abstract: Uptake transporters in the basolateral membrane of hepatocytes are important for the hepatobiliary elimination of drugs. Further, since drug-metabolizing enzymes are located intracellularly, uptake into hepatocytes is a prerequisite for their subsequent metabolism. Therefore, alteration of uptake transporter function (e.g., by concomitantly administered drugs or due to functional consequences of genetic variations, leading to reduced transport function) may result in a change in drug pharmacokinetics. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 148 publications
1
67
1
1
Order By: Relevance
“…An important mechanism of drug-drug interactions is inhibition of drug uptake by a second, concomitantly administered drug (for review, see Fahrmayr et al, 2010). Because we were able to show that mesalazine is a substrate of OATP1B1, OATP1B3, and OATP2B1, we determined the impact of drugs known to inhibit OATPs and of other drugs used for treatment of inflammatory bowel disease on OATP1B1-, OATP1B3-, and OATP2B1-mediated mesalazine uptake.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An important mechanism of drug-drug interactions is inhibition of drug uptake by a second, concomitantly administered drug (for review, see Fahrmayr et al, 2010). Because we were able to show that mesalazine is a substrate of OATP1B1, OATP1B3, and OATP2B1, we determined the impact of drugs known to inhibit OATPs and of other drugs used for treatment of inflammatory bowel disease on OATP1B1-, OATP1B3-, and OATP2B1-mediated mesalazine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that mesalazine delivered from the portal venous blood to the liver will be taken up by OATP1B1, OATP1B3, and OATP2B1 localized in the basolateral membrane of hepatocytes (K m values 55.1, 77.4, and 188.9 M, respectively). Genetic variations in the SLCO1B1 gene encoding for mutated OATP1B1 proteins, in particular the variants SLCO1B1*5 and *15, affect the plasma concentrations, therapeutic effects, and side effects of a broad variety of drugs, including statins and certain oral antidiabetic drugs (Fahrmayr et al, 2010). For example, recent studies reported a strong dependence of simvastatin acid plasma concentrations on the SLCO1B1 genotype (Pasanen et al, 2006) and a clear relationship between SLCO1B1 variants and the risk for statin-induced myopathy (Link et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations